Effect of Lactobacillus acidophilus Supernatant on the Biofilm Formation of Some Pathogenic Bacteria (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study included the investigation of the ability of some gram-positive and gram-negative bacterial species to produce viscous layer which plays a role in biofilm formation and complication of pathogenic infections and resistance to antibiotic therapy.Forty-five bacterial isolates were used in this study, they include Escherichia coli(13 isolates), Staphylococcus aureus(10 isolates), Acintobacter baummanni (10 isolates), Klebsiella pneumonia (7 isolates) and Enterobacter aerogines (5 isolates).Two methods were used to detect biofilm production which includes: Congo red agar medium (CRA) and Microtiter (MTP) method.The results showed that the Microtiter plate method was more sensitive for slime layer detection as the rate of production was 48.88% from all isolates as compared with 42.22% positive results in Congo red agar method. There are clear differences in moderate and negative results for both methods.Also, study resistance isolates to antibiotics, The results showed that                                                  all isolates were 100% sensitive to Imipenem and Amikacin, while the isolates were resistance 28.8% to Tobramycin,  whereas Norfloxacin resistance was only by Acintobacter baummanni, with 22.2%, While the ratio of resistant of isolates to gentamicin was 31.1%.